Medical Imaging 2023: Physics of Medical Imaging 2023
DOI: 10.1117/12.2654449
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dual-energy imaging of bone marrow edema using multi-source cone-beam CT with model-based decomposition

Abstract: Purpose:We investigated the feasibility of dual-energy (DE) detection of bone marrow edema (BME) using a dedicated extremity cone-beam CT (CBCT) with a unique three-source x-ray unit. The sources can be operated at different energies to enable single-scan DE acquisitions. However, they are arranged parallel to the axis of rotation, resulting in incomplete sampling and precluding the application of DE projection-domain decompositions (PDD) for beam-hardening reduction. Therefore, we propose a novel combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Even smaller water content changes might be discernible in smaller body parts and using narrower collimation or additional means of scatter reduction such as antiscatter grids or extended scan geometries. Additional performance improvements might be possible by adopting advanced model-based decomposition algorithms (VCP-constrained one-step decompositions 33,34 with proper initializations such as the result of the complete PDD-to-IDD approach, or unconstrained decompositions replacing the PE-Al twomaterial PDD step 31 ) and data-driven scatter estimation methods 70,71 in place of the analytical and MC-based approaches investigated in the current work. The results of this feasibility study pave the way for performance evaluation in humans and live animal models in the settings of acute BME.…”
Section: Bme Bmementioning
confidence: 99%
See 1 more Smart Citation
“…Even smaller water content changes might be discernible in smaller body parts and using narrower collimation or additional means of scatter reduction such as antiscatter grids or extended scan geometries. Additional performance improvements might be possible by adopting advanced model-based decomposition algorithms (VCP-constrained one-step decompositions 33,34 with proper initializations such as the result of the complete PDD-to-IDD approach, or unconstrained decompositions replacing the PE-Al twomaterial PDD step 31 ) and data-driven scatter estimation methods 70,71 in place of the analytical and MC-based approaches investigated in the current work. The results of this feasibility study pave the way for performance evaluation in humans and live animal models in the settings of acute BME.…”
Section: Bme Bmementioning
confidence: 99%
“…Therefore, the imaging chain non-idealities that are often associated with CBCT-ranging from relatively high electronic noise and limited dynamic range of flat-panel detectors (FPD), to FPD lag and glare, 28 to x-ray scatter-remain a substantial challenge in the development of DE CBCT techniques. Nevertheless, our initial simulation studies [29][30][31] demonstrated that BME can be detected in DE CBCT as long as the scatter is controlled using either a grid or a modest collimation (≤ 15 cm); any residual scatter needs to be corrected to within 10% magnitude. In this work, we build on these preliminary investigations to present the first experimental evaluation of BME imaging using DE CBCT with a comprehensive artifact correction framework, including fast Monte Carlo (MC) scatter estimation.…”
Section: Introductionmentioning
confidence: 99%